Revised Ordinances of the City of Fitchburg Approved February 7, 1893, with the City Charter, the Rules and Orders of the City Council and of Each of the Two Branches, the Special Statutes, a List of General Statutes Adopted or Accepted, Together with an Index, at 179 Fitchburg Revised Ordinances. §§ 75-76 (1893) - (:unkn) unknown (General Publisher, 1893)
No person shall sell or keep for sale, within the limits of the city of Fitchburg, any toy pistol, toy cannon, or any other such article in which explosive compounds of any kind are used, or of which such compounds form a part. § 76. No person shall have, use, explode, fire off or discharge, within the limits of the city of Fitchburg, any toy pistol, toy cannon, or any other such article in which explosive compounds of any kind are used, or of which such compounds form a part.
--
Keywords: TRANSFER; MANUFACTURE & POSSESSION - TOYS AND EXPLOSIVES; DISCHARGE